Lessons from the titans what companies in the new economy can learn from the great industrial giants to drive sustainable success - Davis, Scott; Copeland, Carter; Wertheimer, Rob (McGraw-Hill, 2020)
"Three top Wall Street analysts reveal enduring lessons in sustainable success from the great industrial titans-the high-tech companies of their day-to the disruptors that now dominate the economy. Before Silicon Valley disrupted the world with new technologies and business models, America's industrial giants paved the way. Companies like General Electric, United Technologies, and Caterpillar were the Google and Amazon of their day, setting gold standards in innovation, growth, and profitability. Today's leaders can learn a great deal from their successes, as well as their missteps. In this essential guide, three veteran Wall Street analysts reveal timeless lessons from the titans of industry-and offer battle-tested survival tactics for an ever-changing world, among them: How GE became the largest company on earth-and faced the largest collapse in history. How Honeywell recommitted to product development-and rebounded in the new economy. How Boeing reassessed risks, raised profits-and learned the dangers of success. How Danaher pivoted to innovation when its old winning formula no longer worked-and maintained its strength. How Caterpillar overcame the complacency of being a market leader-and turned its declining fortunes around. Through illuminating case studies, business leaders and entrepreneurs will discover invaluable insights into weathering market upheavals as well as hard-won lessons in innovation, growth, resilience, and operational excellence. This is how manufacturers survived the disruptors of technology-and how today's giants can survive and thrive during the next inevitable disruption"--